2020
DOI: 10.1002/joa3.12457
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in quality of life and cardiac function after catheter ablation for asymptomatic persistent atrial fibrillation

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Clinical trials on intervention treatment strategies (rate or rhythm control) demonstrated lower HRQoL values for patients with AF compared to the general population or control groups [24,25]. The effect of the use of ablation [26] and cardioversion [27] on the sense of quality of life in AF has also been documented.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials on intervention treatment strategies (rate or rhythm control) demonstrated lower HRQoL values for patients with AF compared to the general population or control groups [24,25]. The effect of the use of ablation [26] and cardioversion [27] on the sense of quality of life in AF has also been documented.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that catheter ablation makes asymptomatic atrial fibrillation patients more healthconscious, which leads to better medication adherence, lower salt-sensitive hypertension, and thus improved cardiac function. It also reduced mental anxiety and activity limits, which helped improve the quality of life (73). However, another study suggests that anxiety and depression in patients with the acute coronary syndrome who underwent PCI were associated with increased length of hospital stay (74).…”
Section: Discussionmentioning
confidence: 99%
“…If assessed in more detail, such as using validated questionnaires, AF-related symptoms could be found (or compared). Therefore, several reports have documented improvements in QoL, as assessed using a standardized questionnaire, after CA of asymptomatic persistent AF patients 38,39 . Even though current ESC guidelines remain restrictive with their recommendations on CA for non-paroxysmal AF, these patients seem to benefit more from the procedure than paroxysmal patients.…”
Section: The Effect Of Catheter Ablation On Quality Of Life In Non-pa...mentioning
confidence: 99%